Analisis Kebutuhan Pengembangan E-LKPD Berbasis PBL Materi Sistem Pencernaan Makanan SMAN 1 2x11 Enam Lingkung - Fathanah Fahzi Hasibuan; Lufri Lufri (Lembaga Yasin AlSys, 2025)
Education is a fundamental human necessity that is essential for personal development and for preparing individuals to face future challenges, including the impact of advances in science and technology on the development of high-quality and intelligent human resources. This study aims to analyze the needs for developing Problem-Based Learning (PBL)-based Electronic Student Worksheets (E-LKPD) on the topic of the human digestive system. It constitutes a preliminary study within the Four-D development model, with research subjects comprising one biology teacher and 31 Grade XI F2 students at SMAN 1 2x11 Enam Lingkung. Data were collected through interviews and observation questionnaires, then analyzed descriptively using both qualitative and quantitative approaches. The results indicate an urgent need for interactive and visual teaching materials; the majority of students (90.3%) require learning resources that are comprehensive, concise, and clear, with strong emphasis on attractive visual elements (74.2%) and linguistic clarity (83.9%). Furthermore, 87.1% of students agreed with the development of PBL-based E-LKPD as a solution. The study concludes that the development of PBL-based E-LKPD is necessary to transform learning from passive to active. Practical and flexible E-LKPD, when combined with the PBL model, has the potential to effectively foster critical thinking and problem-solving skills. The implication is that E-LKPD should be designed with multimedia features (videos/images) capable of visualizing abstract concepts in accordance with the E-LKPD design framework, thereby supporting active, contextual biology learning that is aligned with the demands of twenty-first-century education.